2006
DOI: 10.1063/1.2186324
|View full text |Cite
|
Sign up to set email alerts
|

Free-energy analysis of solubilization in micelle

Abstract: A statistical-mechanical treatment of the solubilization in micelle is presented in combination with molecular simulation. The micellar solution is viewed as an inhomogeneous and partially finite, mixed solvent system, and the method of energy representation is employed to evaluate the free-energy change for insertion of a solute into the micelle inside with a realistic set of potential functions. Methane, benzene, and ethylbenzene are adopted as model hydrophobic solutes to analyze the solubilization in sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 54 publications
6
89
0
Order By: Relevance
“…The ρ(r) obtained in the present study is in very good agreement with the results of other studies. 16,42,43 For instance, the peak position of the sulfate ion of the SDS micelle is almost the same as that calculated by Matubayasi et al 16 Furthermore, as in the previous studies, a low-density region is observed at the center of the SDS micelle in the present work. These results indicate that our calculations have been performed correctly.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The ρ(r) obtained in the present study is in very good agreement with the results of other studies. 16,42,43 For instance, the peak position of the sulfate ion of the SDS micelle is almost the same as that calculated by Matubayasi et al 16 Furthermore, as in the previous studies, a low-density region is observed at the center of the SDS micelle in the present work. These results indicate that our calculations have been performed correctly.…”
Section: Resultssupporting
confidence: 78%
“…In our previous work, the free energy of transfer, G, of methane from bulk water to the SDS micelle core rather than the free energy profile G(r) was calculated using the thermodynamic integration method with respect to the potential parameters. The free energy profile G(r) for methane solubilization was also evaluated approximately by Matubayasi et al 16 using distribution function theory combined with MD calculations. The results are also plotted in Fig.…”
Section: B Free Energy Profile For Penetrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy-representation method provides a universal computational and theoretical platform for calculation of thermodynamic parameters of solvation and has been already applied to a range of different systems: supercritical fluids, air-water interfaces, micelles, lipid membranes, proteins, and QM/MM systems. 129,[374][375][376][377][378][379][380][381][382][383]385 The approximation used in the current version of energy-representation method is simply PY-type and HNC-type ones over the energy coordinate, however, it is considered a new class of bridge functional since the coordi-nate (abscissa) of distribution function has been switched from distance to energy. The connection between spatial coordinate-based and energy-based approaches can be an interesting topic of investigation.…”
Section: Note On Alternative Distribution-function Approachesmentioning
confidence: 99%
“…a variety of structure formations of the surfactant molecules in water [1][2][3][4]. Recently, several molecular dynamics (MD) calculations have been done for spherical micelles formed in water, which leads the researcher's interest to the structure and dynamics at a molecular level [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%